2020
DOI: 10.3390/ijms21082732
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Single and Double Mutants in Human Glucose-6-Phosphate Dehydrogenase Variants Present in the Mexican Population: Biochemical and Structural Analysis

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most frequent human enzymopathy, affecting over 400 million people globally. Worldwide, 217 mutations have been reported at the genetic level, and only 19 have been found in Mexico. The objective of this work was to contribute to the knowledge of the function and structure of three single natural variants (G6PD A+, G6PD San Luis Potosi, and G6PD Guadalajara) and a double mutant (G6PD Mount Sinai), each localized in a different region of the three-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(55 citation statements)
references
References 32 publications
1
54
0
Order By: Relevance
“…This increase in motion may lead to increased molecular stresses which overall reduce stability. This is supported by previous work showing ABEN having a cooperative impact on the reduction of enzyme stability when in combination with ADEL, and other G6PD variants [28] , [29] . These molecular interpretations correlate with clinical evidence that showed the ABEN variant to be a genetic modifier of the impact induced by ADEL on enzyme activity and risk of G6PD deficiency [30] .…”
Section: Discussionsupporting
confidence: 84%
“…This increase in motion may lead to increased molecular stresses which overall reduce stability. This is supported by previous work showing ABEN having a cooperative impact on the reduction of enzyme stability when in combination with ADEL, and other G6PD variants [28] , [29] . These molecular interpretations correlate with clinical evidence that showed the ABEN variant to be a genetic modifier of the impact induced by ADEL on enzyme activity and risk of G6PD deficiency [30] .…”
Section: Discussionsupporting
confidence: 84%
“…G6PD A +376G , typically classified as an asymptomatic class IV G6PD deficiency variant (Luzzatto et al, 2020), was recently considered a class III variant. According to in vitro findings by Gómez-Manzo et al (2015), it produces a thermolabile mutated protein with 50% catalytic efficiency due to the alteration of its functional and structural stability (Gómez-Manzo et al, 2015;Martínez-Rosas et al, 2020). This suggests that this variant may have been involved in producing positive G6PD test results for the patients in this study; however, additional mutations in the G6PD gene remain to be identified.…”
Section: G6pd Variants In Mexicansmentioning
confidence: 71%
“…Glucose-6-phosphate-dehydrogenase (G6PD) is a housekeeping cytosolic enzyme in all life forms, from prokaryotes to animals. It catalyzes the first rate-limiting step of the oxidative phase in the PPP [13,14]. The T. vaginalis g6pd gene is fused with the gene that codes for 6-phosphogluconolactonase (GPGL), giving rise to a fused G6PD::6PGL protein.…”
Section: Introductionmentioning
confidence: 99%